1478 Attendances at the Children's Emergency Department: An Audit of two Years of Activity at a New, Dedicated Paediatric Emergency Department. (October 2012) - Isba, R; Gibb, M; Rowland, AG
Abstract : Aim: The aim of this audit was to explore patterns of attendance at a new, dedicated, audio-visually separate paediatric emergency department (PED) within the ED of a hospital in the North West of England. The PED was opened in June 2009 following the major restructuring of paediatric services in Manchester. Methods: This was a retrospective audit of paediatric attendances (those aged < 16 years) to the ED of North Manchester General Hospital between June 2009 and June 2011. Results: During the first year there were 26073 attendances to the PED, while in the second there were 24119 (just over a quarter of all attendances to the ED). More than half of all attendees were in the pre-school age group. There were low levels of attendance overnight, and numbers of attendees peaked around 6pm. Mondays were the busiest days (mean attendees 75.4) and Fridays the quietest (mean attendees 64.6). Whilst the average length of stay was just over two hours, this varied depending on the time of arrival. Approximately one in six children was referred to an inpatient specialty for further assessment. Conclusion: These results have implications for those managing EDs that care for children. Knowledge of attendance patterns may enable managers to better plan staffing levels and deployment within an ED, and there are wider implications for the hospital as a whole. By gaining a better understanding of the patterns of attendance it may be possible to predict future patterns (e.g. via mathematical modelling), and to plan resources accordingly.